FIGURE 6 in Ranunculus schmalhausenii (section Batrachium, Ranunculaceae), a neglected water crowfoot endemic to Fennoscandia-a case of rapid hybrid speciation in postglacial environment of North Europe - Bobrov, Alexander A.; Zalewska-Gałosz, Joanna; Jopek, Magdalena; Movergoz, Ekaterina A. (Zenodo, 2015)
FIGURE 6. Ranunculus schmalhausenii in the wild in Republic of Karelia, Russia: A—plant in deep water of lake Srednee Kuito (vicinity of town Kalevala), B—whole plant in the shallow of lake Bolshoe Severnoe (vicinity of village Sosnovyi), C, D—floating upper vegetativegenerative part in the shallow of lake Bolshoe Severnoe (vicinity of village Sosnovyi). Photos A.A. Bobrov, (A) 16 July 2012, (B–D) 17 July 2012. Published as part of Bobrov, Alexander A., Zalewska-Gałosz, Joanna, Jopek, Magdalena & Movergoz, Ekaterina A., 2015, Ranunculus schmalhausenii (section Batrachium, Ranunculaceae), a neglected water crowfoot endemic to Fennoscandia-a case of rapid hybrid speciation in postglacial environment of North Europe, pp. 101-138 in Phytotaxa 233 (2) on page 123, DOI:10.11646/phytotaxa.233.2.1, http://zenodo.org/record/13633301